REMOTE LEARNING: A WORLD-WIDE-WEB OPERATED ROBOT ARM - Elchanani, Matanya; Sobh, Tarek M.; Mihali, Raul (International Journal of Computing, 2014)
The World-Wide-Web has been used extensively in the past few years of its existence for data exchange, and information gathering. Web online control, on the other hand, is a new emerging field, which has not yet been fully exploited and holds in it a great impact on currently available control systems. This paper discusses an application of online Internet control service - a WWW controlled robotic manipulator arm.